Rerounding of Deflected Thermoplastic Conduit in Well-Graded Aggregate Backfill. Issue 1 (January 2023) - White, Kevin; Sargand, Shad; Khoury, Issam
Rerounding is a technique for remediating excess deflection in thermoplastic pipe using a pneumatic device vibrating along the vertical axis and pushing against the inside crown and invert to restore the original pipe shape and redistribute the surrounding backfill. Since the process has not been evaluated on high density polyethylene (HDPE) pipe outside of a few reports, and the method is routinely used by contractors to remediate deflected thermoplastic pipes, the Ohio Department of Transportation (ODOT) wanted to evaluate the technology as a lower-cost and less disruptive alternative to the removal and reinstallation of deflected pipes. Three 36-in. HDPE pipes were installed in a well-graded crushed stone aggregate, sand, or AASHTO #57 open-graded aggregate (ODOT Structural Backfill, Types 1, 2, and 3, respectively), and two 18-in. pipes were installed in Types 2 and 3 Structural Backfill. Pipes were intentionally installed with substantial deflection (10% or more) and then rerounded. The pipe conditions were measured and monitored by collecting profiles, measuring vertical deflections and monitoring soil pressures, backfill characteristics, and the depth of pipe corrugation before and after rerounding. This paper focuses on Test Pipe 1 installed in Type 1 Structural Backfill, which was the most resistant to rerounding. Pressure data were consistent with the redistribution of backfill particles, particularly fines.